Determination of anodal tDCS duration threshold for reversal of corticospinal excitability: An investigation for induction of counter-regulatory mechanisms - Maryam Hassanzahraee; Michael A. Nitsche; Maryam Zoghi; Shapour Jaberzadeh (Brain Stimulation, 2020)
Background: Transcranial direct current stimulation (tDCS) is used to induce neuroplasticity in the human brain. Within certain limits of stimulation duration, anodal tDCS (a-tDCS) over the primary motor cortex induces long term potentiation- (LTP) like plasticity. A reversal of the direction of plasticity has however been described with prolonged a-tDCS protocols. Objective: We aimed to systematically investigate the intervention duration threshold for reversal of a-tDCS-induced effects on corticospinal excitability (CSE) and to determine the probable mechanisms involved in these changes. Methods: Fifteen healthy participants received a-tDCS of 1 mA for five different durations in pseudo-random session order. Transcranial magnetic stimulation (TMS) was delivered over the left M1, and motor evoked potentials (MEPs) of a contralateral hand muscle were recorded before, immediately and 30 min following intervention to measure CSE changes. Short-interval intracortical inhibition (SICI), intracortical facilitation (ICF), and long interval facilitation (LIF) were assessed via paired-pulse TMS protocols. Results: A-tDCS significantly increased CSE as expected at stimulation durations of 22 and 24 min. However, this effect of a-tDCS on CSE decreased and even reversed when stimulation duration increased to 26, 28, and 30 min. Respective alterations of ICF, LIF, and SICI indicate the involvement of glutamatergic, and GABAergic systems in these effects. Conclusions: These results confirm a duration threshold for reversal of the excitability-enhancing effect of a-tDCS with stimulation durations ≥ 26 min. Counter-regulatory mechanisms are discussed as a mechanistic foundation for these effects, which might prevent excessive brain activation.